MRI signal changes and their association with intervertebral disc disease in canine vertebral endplates - Emma Deards; Dylan N. Clements; Tobias Schwarz (Irish Veterinary Journal, 2019)
Abstract Background This study was undertaken to determine the relationship between intervertebral endplate changes and intervertebral disc disease. This study was designed as a cross-sectional, observational study. Two hundred thirteen canine MRI scans performed between 2007 and 2014 were retrieved from a digital image archive. Scans which included any sagittal sections of the vertebral column from C1 to S1 were assessed for morphological changes to the vertebral endplate. Results There was found to be a significant association between vertebral endplate changes and intervertebral disc disease of the adjacent disc (P = 0.021). There was not found to be any significant association between dogs having vertebral endplate changes and having intervertebral disc disease (P = 0.38). There was found to be a highly significant association between discs with vertebral endplate changes on both associated vertebrae (bilateral) and having intervertebral disc disease (P = < 0.0001). Conclusions The presence of endplate changes should alert the observer to closely examine the disc, as intervertebral disc disease is mildly more likely to occur adjacent to these changes.